Using Boardgames as Classroom-based Assessment in TBLT in State-funded Schools in Chile: an exploratory discussion - Peralta, Bruno Paulo (Contextos: Estudios de Humanidades y Ciencias Sociales, 2023)
Assessment and education have a close relation within a country’s system, as it is shown in Chile by a dominating neoliberal policy (Gysling, 2015), which permeates the way education is perceived and realized, through control and manipulation (Fulcher, 2010). Because of this, large-scale testing has a clear advantage and influence, as opposed to classroom-based assessment (CBA). However, this large-scale testing view has ignored what is produced and done in a classroom, as the results of large-scale testing do not necessarily represent an EFL classroom (Turner, 2012). In this case, the need for research and development of CBA is required. Consequently, due to their nature, boardgames are proposed as an appropriate tool that can help teachers promote CBA, support task-based language teaching (TBLT), and provide valuable feedback, which is a key component in CBA.